Sharing hidden know-how : how managers solve thorny problems with the knowledge jam - Pugh, Katrina (J-b us non-franchise leadership, 2011)
"One of the great management ideas of the last fifteen years has been to make use of the knowledge that an organization has already learned. This book's five-step process, which the author calls Knowledge Jam, shows how to set the direction, foster the correct tone, conduct a knowledge capture event, and integrate this knowledge into the organization. It also introduces conversation practices for participants to effectively co-create knowledge and discover context. Rich with case studies, how-to templates, and adaptations, this book is ideal for external consultants, internal facilitators and leaders"--Provided by publisher.